PTK Penerapan Teams Games Tournamen Berbantuan Paksi (Papan Kreasi) Untuk Meningkatkan Keaktifan Belajar Siswa Kelas XI-9 SMAN 8 Denpasar - Davia Faringggasari, Rulianto (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2026)
ABSTRACT This study aims to increase the learning activeness of students in class XI-9 SMAN 8 Denpasar through TGT (Team Game Tournament) cooperative learning model assisted by PAKSI (Creation Board) on the material of Proclamation of Indonesian Independence. Based on the results of observations, researchers will follow up on the problem of less active classes and few students participating in learning activities in class XI-9. This research uses the type of classroom action research (PTK) with pre-cycle and two cycles, each of which consists of planning, action, observation, and reflection stages. The subjects of this study amounted to 40 people. This class action research uses data collection techniques through observation, questionnaires, interviews and documentation. Quantitative data analysis techniques to analyze student activeness with the results of observation sheets of learning activities after using the Team Game Tournament (TGT) cooperative learning model assisted by PAKSI (Creation Board). The results of the research in the pre-cycle, the majority of students (90%) were classified as poor in learning activeness. After the application of the TGT model, there was an increase in cycle 1 with 5% of students in the very good category and 27.5% in the good category. A significant increase occurred in cycle 2, with 42.5% of students classified as very good and 52.5% good, while only 5% were still not good. These results show that the TGT model assisted by PAKSI is effective in increasing student learning activeness. Keywords: Teams Games Tournament, PAKSI, Learning Activity, History Learning